2003
DOI: 10.1213/01.ane.0000072705.86142.5d
|View full text |Cite
|
Sign up to set email alerts
|

Onset Time, Quality of Blockade, and Duration of Three-in-One Blocks with Levobupivacaine and Bupivacaine

Abstract: Levobupivacaine is the isolated S(-)-stereoisomer of racemic bupivacaine. Important pharmacodynamic properties of levobupivacaine have not been determined for the femoral three-in-one block. In this randomized, controlled, double-blinded trial, we studied 60 ASA physical status I-III patients scheduled for surgery of the lower limb. A nerve-stimulator-guided three-in-one block was performed as supplemental analgesic therapy with 20 mL of bupivacaine 0.5% (n = 20), levobupivacaine 0.5% (n = 20), or levobupivaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
(22 reference statements)
0
39
0
1
Order By: Relevance
“…Studies on sensory onset time, quality of sensory block, and duration of peripheral nerve block with levobupivacaine have shown different results. This more frequent rate may be explained by differences in the local anesthetic volume (20 ml vs 0.4 ml/kg) or by slight methodological differences in the assessment of blockade [4,14,15]. Pippa et al [16] concluded that a lower concentration of anesthetic solution avoids complications, while an increased volume provides good analgesic cover.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sensory onset time, quality of sensory block, and duration of peripheral nerve block with levobupivacaine have shown different results. This more frequent rate may be explained by differences in the local anesthetic volume (20 ml vs 0.4 ml/kg) or by slight methodological differences in the assessment of blockade [4,14,15]. Pippa et al [16] concluded that a lower concentration of anesthetic solution avoids complications, while an increased volume provides good analgesic cover.…”
Section: Discussionmentioning
confidence: 99%
“…5,23,24 In this study FNB was performed with 1.5% lignocaine and time to onset was 5 min with a peak at 12 minutes. It can be reasoned out by the fact that FNB produced relaxation of the quadriceps muscle and hence provided better analgesia for positioning and a shorter time to perform spinal anesthesia.…”
mentioning
confidence: 99%
“…21 The analgesic effect of lignocaine comes within 5 mins while it takes 20-30 minutes for bupivacaine to come into effect. 8,22,23 The analgesic affect of FNB was better than that of IVF, with more number of patient's satisfaction as was seen with Jadon et al while Iamaroon et al found no difference in the two drugs. The time taken to perform the anesthesia was also significantly lower in the FNB group as compared to the IVF group, as with a study by Jadon et al…”
Section: Discussionmentioning
confidence: 84%